2016
DOI: 10.1134/s0012496616040013
|View full text |Cite
|
Sign up to set email alerts
|

The role of neighborhood relations in maintenance of the spatial–ethological structure of local settlements as exemplified by the water vole (Arvicola amphibius)

Abstract: Adult males of the water vole have been found experimentally to recognize their neighbors and react to them differently depending on the degree of spatial proximity in nature. Most tensions (estimated by the number of aggressive acts in the encounters) were observed between distant neighbors (from neighboring settlements), which did not belong to the same groups with established hierarchy and a relatively reduced aggression. These are probably perceived as the most likely competitors (because of their spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nevertheless, we found that a clear 12-year cycle is manifested in the Tomsk Region, whereas in our studies, surges in water vole numbers were observed between the intervals of 35 years. Some studies show that in conditions of anthropogenic transformation, in particular, under the influence of agriculture, the natural rhythm of population dynamics and the nature of its peaks are disrupted (Nazarova & Evsikov, 2012;Litvinov et al, 2013;Erdakov & Litvinov, 2014;Evsikov et al, 2016;Meulemans, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we found that a clear 12-year cycle is manifested in the Tomsk Region, whereas in our studies, surges in water vole numbers were observed between the intervals of 35 years. Some studies show that in conditions of anthropogenic transformation, in particular, under the influence of agriculture, the natural rhythm of population dynamics and the nature of its peaks are disrupted (Nazarova & Evsikov, 2012;Litvinov et al, 2013;Erdakov & Litvinov, 2014;Evsikov et al, 2016;Meulemans, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…According to the research in the Barabinskaya forest-steppe, water voles form local reproductive settlements, including potential competitors for food and reproductive resources. Therefore, a decrease or increase in aggression towards neighboring individuals is a condition for the relative stability of settlements and their effective preservation over time (Nazarova et al, 2012;Evsikov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%